Financing Public Capital through Land Rent Taxation: A Macroeconomic Henry George Theorem - Linus Mattauch; Jan Siegmeier; Ottmar Edenhofer; Felix Creutzig (Center for Economic Studies and ifo Institute (CESifo), 2013)
Financing productive public capital through distortionary taxes typically creates a trade-off: the optimal investment is determined as a compromise between efficiency-enhancing public investment and perturbing market efficiency, but is never socially optimal. In contrast, such a trade-off can often be avoided if public capital is financed by taxing rents of a fixed production factor, such as land. Here, we provide a macroeconomic version of the Henry George Theorem. Specifically, we prove that the socially optimal level of the public capital stock can be reached by a land rent tax, provided land is a more important production factor than public capital.
Keywords: H21; H40; H54; Q24; 330; land rent tax; public investment; Henry George Theorem; social optimum